2018
DOI: 10.1097/nnr.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Relationships Between Postoperative Pain and Subsyndromal Delirium in Older Adults

Abstract: Higher pain levels were significantly related to subsyndromal delirium when age, cognitive status, smoking status, and opioid intake were accounted for (p < .05), although opioid intake was not significantly related to subsyndromal delirium after accounting for age, cognitive status, smoking status, and pain. Nurses caring for older adults who undergo joint replacement surgery are encouraged to ensure effective pain management to reduce onset and severity of delirium symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
2
11
0
1
Order By: Relevance
“…In previous studies these factors were associated with delirium: functional impairment (3,26,34) pain (26,35), low hemoglobin or hematocrit level (26,34,36), hyponatremia (37,38), and hypocalcemia (32,39). In studies of risk factors for SSD an association was found with some of the same factors that were significantly associated with it in the present study in univariate analyses, including functional impairment (7,18), pain (40), and hyponatremia (18).…”
Section: Risk Factors For Deliriumsupporting
confidence: 74%
“…In previous studies these factors were associated with delirium: functional impairment (3,26,34) pain (26,35), low hemoglobin or hematocrit level (26,34,36), hyponatremia (37,38), and hypocalcemia (32,39). In studies of risk factors for SSD an association was found with some of the same factors that were significantly associated with it in the present study in univariate analyses, including functional impairment (7,18), pain (40), and hyponatremia (18).…”
Section: Risk Factors For Deliriumsupporting
confidence: 74%
“…A recent study found that BIS-guided deep anesthesia reduced early postoperative cognitive decline and inhibited postoperative peripheral inflammation in elderly patients [ 46 ]. A third limitation involves pain severity, which is a known factor associated with PD [ 47 ]. The quality and the type of analgesia were not taken into account in our study because all patients were given sufentanil 0.1 μg/kg at about 30 min before the end of the surgery, patient-controlled intravenous or epidural analgesia, and additional analgesics as needed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, nearly seven of 10 participants developing subsyndromal delirium (68%, n = 36), whereas 17% ( n = 9) developed delirium. In studies examining subsyndromal delirium in older adults, incidence rates vary between studies from 27% to 69% in hospitalized older adults following noncardiac surgery (Denny & Such, 2018; Liptzin et al, 2005; Shim et al, 2015). However, the sample sizes of these previous studies varied widely from 49 to 615.…”
Section: Discussionmentioning
confidence: 99%